KARAKTERISTIK GAMBUT RAWA PENING DAN POTENSINYA SEBAGAI BAHAN PEMBAWA MIKROBA - Prihastuti Prihastuti (Research Center for Biology-Indonesian Institute of Sciences, 2013)
This is a descriptive analytical research to describe characteristic of peat soils of Rawa Pening (a natural lake in Central Java, Indonesia). The purpose of this study was to determine the potency of peat soils as a microbial carrier. The parameters observed were chemical properties (pH, levels of C, N, P, K and CEC) and biological properties (total of soil microbial population), as well as its amendments by sun drying,ovens drying and sterilization process by autoclaving (121oC, and 1.5 atm for 15 minutes). The results showed that the Rawa Pening peat soil content consisted of high organic C, medium-high N, low-medium P, high K and high CEC. Total of soil microbial population was quite high, but it was reduced by sun drying and autoclave sterilization. The population of soil microbial was pressured by oven drying, but the process makes it a low pH caused by cell lysis. The Rawa Pening peat soils had physical properties that were not easily changed, is also not prone to changes in pH during the process by sun drying and sterilization by autoclave. It was concluded that the Rawa Pening peat soils have a potential to be a microbial carrier, since it contained high organic matter, and relatively easy to process.